Strategi Pemasaran P.T.Samsung Electronic Indonesia Divisi HHP Cabang Makassar - Hasniaty A (Universitas Muhammadiyah Pontianak, 2015)
This study aims to assess the marketing strategy undertaken by PTSamsung Electronic Indonesia Makassar Branch HHP Division. The company's ability to innovate in the field of the product should be followed by marketing capabilities so that innovative products can still run. The study used a qualitative approach with a SWOT analysis to get an overview of the strategy being executed. Results of the study revealed that there are 5 secrets of Samsung became the world smartphone manufacturers, namely Strengthening Brand Products, Smartphone Specifications, Advertising and marketing, cooperation with the Telecommunications Operator.